2019
DOI: 10.4236/aa.2019.93010
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Mall Culture and Shopping Behavior of Young Consumers

Abstract: Malls are attracting the young shoppers and mall culture is new to the society. Mall retailers are making efforts to satisfy the young consumers. However, the younger segment is growing in terms of population and wealth. It has become increasingly important and necessary to understand and meet their demands. The study employed 160 in-depth interviews to understand the young consumers' mall experiences. Overall, the respondents in the study have favourable perception of the mall in terms of convenience, variety… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 33 publications
(45 reference statements)
1
4
0
Order By: Relevance
“…The explanation here may be that consumers mainly value convenience, comfort and an attractive and wide assortment. This is also confirmed by the research of other authors (Borusiak et al, 2018;Bawa et al, 2019;Klapilová Krbová, 2016;Kunc et al, 2012). On the other hand, the surveyed consumers are not emotionally attached to the shopping center they visit, perceiving it only as a place to perform necessary duties, not a pleasure.…”
Section: Discussionsupporting
confidence: 87%
“…The explanation here may be that consumers mainly value convenience, comfort and an attractive and wide assortment. This is also confirmed by the research of other authors (Borusiak et al, 2018;Bawa et al, 2019;Klapilová Krbová, 2016;Kunc et al, 2012). On the other hand, the surveyed consumers are not emotionally attached to the shopping center they visit, perceiving it only as a place to perform necessary duties, not a pleasure.…”
Section: Discussionsupporting
confidence: 87%
“…A qualitative study of young consumers’ perception of the shopping mall found that participants preferred shopping in the mall because of its convenience, variety of choices, brands consciousness, as well as esthetics and hedonic reasons. The eight factors that were important to form an impression of the shopping malls included convenience, choice, reputation, crowdedness, ambiance, parking, hedonic shopping and mall culture (Bawa et al , 2019). Another study found that the traffic and locality of the mall, parking facilities, as well as inclusive facilities for the disabled had the largest impact on mall preference among young consumers (Can et al , 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The young consumer market segment is growing in terms of size and market value (Bawa et al , 2019). Previous studies indicated that young consumers had unique characteristics in their shopping decision-making styles, including perfectionism, being confused by over-choice, recreational-hedonism, brand consciousness and brand loyalty (Bakewell and Mitchell, 2003; Lysonski et al , 1996).…”
Section: Introductionmentioning
confidence: 99%
“…According to Parking Network [9], the available parking bays in Sunway Pyramid is more than 10,000 and the average daily traffic volume is 50,000 vehicles. The average time spent by shoppers in the mall is from 2 to 3 hours [10], [11], [12]. With greater traffic volume and a higher parking turnover rate, greater energy harvesting can be expected.…”
Section: Introductionmentioning
confidence: 99%